PENGATURAN DALUWARSA DALAM PENYIDIKAN PERUSAKAN SITUS CAGAR BUDAYA (STUDI BALAI PELESTARIAN KEBUDAYAAN WILAYAH X) - Shannon Galice Sofyani (2024)
Cultural heritage is one of Indonesia's wealth that must be maintained and preserved by all components of the nation. Law Number 11 of 2010 concerning Cultural Heritage strengthens efforts to protect and preserve cultural heritage by regulating criminal offences committed against cultural heritage, including cultural heritage destruction. However, investigating criminal offences of destroying cultural heritage sites is inseparable from various problems that can slow down its completion. Therefore, regulating the expiration of the investigation period for cultural heritage destruction needs to be clearly regulated. This research is a normative-empirical research, in which the data is obtained through literature study and interviews with the investigators from the Region X Cultural Preservation Centre. From the research results, it was found that the investigation of the cultural heritage sites destruction still has many obstacles faced. In addition, the expiration of the cultural heritage sites destruction does not yet have a particular regulation and still refers to the Criminal Code.